PENGARUH LITERASI EKONOMI TERHADAP MORALITAS EKONOMI MELALUI RASIONALITAS EKONOMI MAHASISWA PENDIDIKAN EKONOMI UNMUL - Riyo Riyadi (Jurnal Edueco, 2020)
The main problem examined in this research is economic morality. Among adolescents the problem of economic morale is still very low because adolescents usually behave rationally in economics. The aim is to determine (1) the effect of economic literacy on student economic morality, (2) the effect of rationality on student morality, (3) the effect of economic literacy on economic morality through student economic rationality. This research is an explanatory research that aims to explain and analyze certain variables objectively empirical conditions that will be explained and analyzed are the influence of independent variables and dependent variables. This research was designed using a quantitative approach. A sample of 137 students, this research was conducted in the FKIP UNMUL economic education study program. Data collection was carried out using questionnaire and test techniques. The questionnaire technique is used to collect data on rationality and morality. The test is used to collect data about economic literacy. Data analysis was performed using path analysis techniques using the SPSS application. The results of the study concluded: (1) economic literacy has no effect on student economic morality, (2) rationality has an influence on student economic morality, (3) economic literacy has an influence on economic morality in schools through economic rationality.